2021
DOI: 10.1186/s13023-020-01664-6
|View full text |Cite
|
Sign up to set email alerts
|

How are patients with rare diseases and their carers in the UK impacted by the way care is coordinated? An exploratory qualitative interview study

Abstract: Background Care coordination is considered important for patients with rare conditions, yet research addressing the impact of care coordination is limited. This study aimed to explore how care coordination (or lack of) impacts on patients and carers. Semi-structured interviews were conducted with 15 patients and carers/parents in the UK, representing a range of rare conditions (including undiagnosed conditions). Transcripts were analysed thematically in an iterative process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 14 publications
9
42
0
Order By: Relevance
“…Our findings on the organisation of professionals for rare conditions supports previous research that indicates the importance of collaboration and MDTs for rare conditions [12,39] and other conditions [40]. Findings also support previous research which indicates a need to join up care appointments from different disciplines and hospitals into one appointment (e.g., condition-specific clinics), in order to facilitate coordination [12,13]. However, findings indicate that collaboration does not always happen in practice and that improvements in collaboration/joined-up working are needed.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings on the organisation of professionals for rare conditions supports previous research that indicates the importance of collaboration and MDTs for rare conditions [12,39] and other conditions [40]. Findings also support previous research which indicates a need to join up care appointments from different disciplines and hospitals into one appointment (e.g., condition-specific clinics), in order to facilitate coordination [12,13]. However, findings indicate that collaboration does not always happen in practice and that improvements in collaboration/joined-up working are needed.…”
Section: Discussionsupporting
confidence: 90%
“…This study is part of a larger mixed-methods research project which aims to explore coordination of care for people living with rare conditions [21]. This study builds on previous aspects of this study [12, 13.…”
Section: Methodsmentioning
confidence: 99%
“…Care coordinators are not new and have previously been widely implemented for adults and children with chronic conditions and mental health conditions in other countries and in the UK [2630]. The finding that patients/carers are sometimes unable to, or do not want to, coordinate their own care is consistent with previous research that has indicated the negative impact coordinating care can have on patients and families [7,31] and of the treatment burden more generally [1,16].…”
Section: Discussionsupporting
confidence: 77%
“…In line with previous research, our respondents outlined how challenging it could be to coordinate care (22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 63%